Key differences between USA and European syncope guidelines - Olshansky, Brian (Henry Stewart Talks, 2021)
US and European analysis of syncope management, How to evaluate syncope, Guidelines on treatment and hospitalization, Syncope case studies, Guidelines regarding further monitoring, Treatment for vasovagal syncope, orthostatic hypotension and arrhythmia